2022
DOI: 10.3390/cells11213477
|View full text |Cite
|
Sign up to set email alerts
|

Tortuous Cardiac Intercalated Discs Modulate Ephaptic Coupling

Abstract: Cardiac ephaptic coupling, a mechanism mediated by negative electric potentials occurring in the narrow intercellular clefts of intercalated discs, can influence action potential propagation by modulating the sodium current. Intercalated discs are highly tortuous due to the mingling of plicate and interplicate regions. To investigate the effect of their convoluted structure on ephaptic coupling, we refined our previous model of an intercalated disc and tested predefined folded geometries, which we parametrized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…An alternative route of conduction from cell to cell is via the extracellular space, referred to as ephaptic coupling. This alternative has been discussed for a very long time (see, e.g., [18,19]) and recent modeling results, emphasizing the importance of the localization of the ion channels, indicate that ephaptic coupling is a viable alternative way of conduction, see, e.g., [3,[20][21][22][23]. A related discussion goes on in computational neurophysiology where the question is whether or not a neuron can set off an excitation wave in a neighboring cell; see [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…An alternative route of conduction from cell to cell is via the extracellular space, referred to as ephaptic coupling. This alternative has been discussed for a very long time (see, e.g., [18,19]) and recent modeling results, emphasizing the importance of the localization of the ion channels, indicate that ephaptic coupling is a viable alternative way of conduction, see, e.g., [3,[20][21][22][23]. A related discussion goes on in computational neurophysiology where the question is whether or not a neuron can set off an excitation wave in a neighboring cell; see [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…This cell-cell coupling occurs in parallel with direct electrical current flowing from cell 1 to cell 2 via gap junctions. The role of ephaptic coupling in cardiac electrical propagation was proposed over 50 years ago [21][22][23][24] , and subsequent computational studies have predicted that conduction depends on key properties governing ephaptic coupling, including the width of the inter-cellular cleft space and the relative fractions of INa at the ID and the lateral membrane 12,[16][17][18][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] . As the clustering of Na + channels at the ID occurs in conjunction with gap junctions, it is difficult to experimentally separate the relative contribution of gap junction and ephaptic coupling mechanisms, motivating computational modeling studies.…”
Section: Introductionmentioning
confidence: 99%
“…However, for stronger gap junctional, a narrow cleft can slow conduction, as the cleft hyperpolarization and post-junctional ID transmembrane potential depolarization can ultimately result in a smaller INa driving force, which in turn reduces peak INa and thus slows conduction, which was termed "self-attenuation." 16 Subsequent studies have found that conduction due to ephaptic coupling can further depend on additional properties, such as the relative fraction of ID-localized INa and total INa conductance (across the whole cell) 25 , and structural properties, including heterogeneous structure within different regions of the ID 26,[40][41][42] , separation between Na + channels and gap junctions on the ID membrane 40,42 , and cell size 25 .…”
Section: Introductionmentioning
confidence: 99%
“…This cell–cell coupling occurs in parallel with direct electrical current flowing from cell 1 to cell 2 via gap junctions. The role of ephaptic coupling in cardiac electrical propagation was proposed over 50 years ago ( Pertsov and Medvinskiĭ, 1976 ; Sperelakis, 1983 ; Sperelakis and Mann, 1977 ; Sperelakis and McConnell, 2002 ), and subsequent computational studies have predicted that conduction depends on key properties governing ephaptic coupling, including the width of the intercellular cleft space and the relative fractions of I Na at the ID and the lateral membrane ( Greer-Short et al, 2017 ; Hand and Peskin, 2010 ; Hichri et al, 2018 ; Ivanovic and Kucera, 2021 ; Ivanovic and Kucera, 2022 ; Kucera et al, 2002 ; Lin and Keener, 2010 , 2013 , 2014 ; Ly and Weinberg, 2022 ; Moise et al, 2021 ; Mori et al, 2008 ; Nowak et al, 2020 ; Nowak et al, 2021a ; Nowak et al, 2021b ; Poelzing et al, 2021 ; Veeraraghavan et al, 2015 , 2016 ; Wei et al, 2016 ; Wei and Tolkacheva, 2022 ; Weinberg, 2017 ; Yu et al, 2022 ). As the clustering of Na + channels at the ID occurs in conjunction with gap junctions, it is difficult to experimentally separate the relative contribution of gap junction and ephaptic coupling mechanisms, motivating computational modeling studies.…”
Section: Introductionmentioning
confidence: 99%
“…However, for a stronger gap junction, a narrow cleft can slow conduction as the cleft hyperpolarization and postjunctional ID transmembrane potential depolarization can ultimately result in a smaller I Na driving force, which in turn reduces peak I Na and thus slows conduction, which was termed “self-attenuation” ( Kucera et al, 2002 ). Subsequent studies have found that conduction due to ephaptic coupling can further depend on additional properties, such as the relative fraction of ID-localized I Na and total I Na conductance (across the whole cell; Nowak et al, 2021a ), and structural properties, including heterogeneous structure within different regions of the ID ( Hichri et al, 2018 ; Ivanovic and Kucera, 2021 ; Ivanovic and Kucera, 2022 ; Moise et al, 2021 ), the separation between Na + channels and gap junctions on the ID membrane ( Hichri et al, 2018 ; Ivanovic and Kucera, 2021 ), and cell size ( Nowak et al, 2021b ).…”
Section: Introductionmentioning
confidence: 99%